PENGARUH TINGKAT KECERDASAAN EMOSIONAL SISWA TERHADAP HASIL BELAJAR SISWA PADA MATA PELJARAN IPA - Firmansyah, Edi; Kamaluddin, Kamaluddin (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2020)
On this research, which is organised at SMP N 5 WOHA, the classes which are being investigated are VIII 1 as the non-action group and VIII 2 as the action group. On this research, the expectation is the student's learning outcome. The research design follows the factorial design. Both groups follow the learning with matery, purpose, the same teacher and learning source. The implementation of learning is different in case of method used. At the level of emotional intelligence, there are some students classify as high and mid category.on analysis result, that student's learning outcome in science lesson is affected by the level of emotional intelligence